2006
DOI: 10.1177/0115426506021003312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ideal Body Weight Equations and Published Height‐Weight Tables With Body Mass Index Tables for Healthy Adults in the United States

Abstract: The purpose of this paper was to compare the ideal body weight (IBW) formulas and published height-weight tables for healthy adults in the United States with the body mass index (BMI) of 22 kg/m2, which is associated with lowest mortality. There are numerous formulas and published height-weight tables available to determine IBW, but there are no published studies comparing the validity of formulas with each other or comparing formulas with BMIs. Data from height-weight tables, weight for specific heights deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 14 publications
1
78
0
3
Order By: Relevance
“…39 This suggests that normal values developed for the general population may not be appropriate for classifying the elderly in terms of mortality risk. It cannot be overlooked, however, that the increased mortality associated with low BMI in the present study may be attributable to preexisting diseases in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…39 This suggests that normal values developed for the general population may not be appropriate for classifying the elderly in terms of mortality risk. It cannot be overlooked, however, that the increased mortality associated with low BMI in the present study may be attributable to preexisting diseases in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal body weight in the present study was defined as the value calculated from the height and a BMI of 22, because of its validity (19), instead of the value calculated with the Lorentz formula used in the original GNRI equation. We compared GNRI scores calculated by both formulae and found that there was little difference between the values (Figure 1).…”
Section: Geriatric Nutritional Risk Indexmentioning
confidence: 99%
“…Mean age at enrollment was 16.0 6 1.7 years (range [12][13][14][15][16][17][18][19] and 93% of the participants were Caucasian. In Table 1, at baseline, the group that subsequently resumed menses was similar to the group that remained amenorrheic with respect to weight, percent median body weight and BMI.…”
Section: As Shown Inmentioning
confidence: 99%